The Effect Of Venn Diagram To Enhance Students Reading Comprehension At The Second Year Of Smp Negeri 1 Wawotobi - Asri Nofa Rama (Jayapangus Press, 2018)
This study aimed to find out (1) the extent to which Venn diagram enhance students’ reading comprehension. This study was a mixed method research design known as explanatory mixed method design (Quan-Qual model). There were two groups involved namely experimental and control group. The study was carried out at the second year of SMP Negeri 1 Wawotobi with 33 students as the sample. Data were collected by using reading test. Moreover, the data were analyzed quantitatively and interpreted by using the software program of SPSS 16.0. This study found that Venn Diagram give a significant effect on students’ reading comprehension from pre-test to post-test revealed the significant difference (0.000< 0.05) before and after the implementation of Venn diagram. This study concludes that Venn diagram enhance students’ reading comprehension at the second year of SMP Negeri 1 Wawotobi.